Potential mechanisms for the effects of tea extracts on the attachment, biofilm formation and cell size of Streptococcus mutans - Wang, Y.; Lee, S.; Dykes, Gary (2013)
Tea can inhibit the attachment of Streptococcus mutans to surfaces and subsequent biofilm formation. Five commercial tea extracts were screened for their ability to inhibit attachment and biofilm formation by two strains of S. mutans on glass and hydroxyapatite surfaces. The mechanisms of these effects were investigated using scanning electron microscopy (SEM) and phytochemical screening. The results indicated that extracts of oolong tea most effectively inhibited attachment and extracts of pu-erh tea most effectively inhibited biofilm formation. SEM images showed that the S. mutans cells treated with extracts of oolong tea, or grown in medium containing extracts of pu-erh tea, were coated with tea components and were larger with more rounded shapes. The coatings on the cells consisted of flavonoids, tannins and indolic compounds. The ratio of tannins to simple phenolics in each of the coating samples was ~3:1. This study suggests potential mechanisms by which tea components may inhibit the attachment and subsequent biofilm formation of S. mutans on tooth surfaces, such as modification of cell surface properties and blocking of the activity of proteins and the structures used by the bacteria to interact with surfaces.